Дьявол носит PRADA: роман / Л. Вайсбергер - Вайсбергер Лорен (АСТ, 2019)
Экземпляры: Селтинская районная библиотека (аб) (20191128) / Инвентарный номер: 206530 / Цена: 100 / Авт.знак: В14 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)